PERNIKAHAN SEDARAH ( INCEST ) DARI PERSPEKTIF ISLAM DAN HUKUM NASIONAL - Surya Putra, Wiene (Jurnal Landraad, 2022)
Incest, often known as incest, is frowned upon in society, although it remains commonplace. This is not a new discovery; it happened throughout the Persian Empire, when some of its kings married their biological mothers or children. That was the demand for religious teachings at that time, based on customs and philosophy. Inbreeding is a flaw in the social order of society because it can disrupt stability and endanger offspring. As a result, Islamic law serves as a mediator, supported by positive regulations, to suppress and reduce inbreeding as much as possible. Environmental conditions are often the cause of inbreeding, especially when the boss has sexual problems that prevent them from meeting family members. Due to the frequency of blood relations that allow the perpetrators to live under the same roof, inbreeding problems are difficult to trace. This is where Islamic criminal law plays an important role in protecting and sanctioning criminals who cross the line. Inbreeding, Incest, and Islamic Criminals are some of the terms used to describe inbreeding.